Periodic payments and rates for vehicular credits and their rates - Rodríguez Beltrán, Francesca Estefanía (2018)
The objective is to analyze the financial concepts that we work for the calculation of the periodic payments, as well as, to calculate the interest and the rates of the vehicular credit, in order to carry out this study, we extracted information from commercial intelligence portals, bank documents, theses and visited different banks located in metropolitan Lima, in this way, we had firsthand knowledge of the different options, modalities and facilities that we present each bank; with all the information obtained and we present here a calculation of the periodic payments and rates for vehicular credits.